Vulnerabilities of Modern Web Applications - Holík, Filip; Neradová, Soňa (IEEE (Institute of Electrical and Electronics Engineers), 2017)
The security of modern web applications is becoming increasingly important with their growing usage. As millions of people use these services, the availability, integrity, and confidentiality are critical. This paper describes the process of penetration testing of these applications. The goal of such testing is to detect application flaws and vulnerabilities and to propose a solution to mitigate them. The paper analyses current penetration testing tools and subsequently tests them on a use case web application, build specifically with present security flaws. The process of penetration testing is described in detail and the performance of each tool is evaluated. In the last section, recommended practices to mitigate found flaws are summarized.
Zranitelnosti moderních webových aplikací
Keywords: Web application security; penetration testing; web application vulnerabilities; Bezpečnost webových aplikací; penetrační testování; zranitelnosti webových aplikací